Upregulated Vav2 in gastric cancer tissues promotes tumor invasion and metastasis - Bi-bo Tan; Yong Li; Li-qiao Fan; Qun Zhao; Qing-wei Liu; Yü Liu; Dong Wang; Nan Jia (Tumor Biology, 2017)
Several studies have proved that Vav2 gene is associated with the carcinogenesis of some tumors, but the relationship between Vav2 gene and gastric cancer remains unclear. Purpose of this study is to detect the expression of Vav2 protein in gastric cancer tissues and to evaluate the clinical value of Vav2 . Furthermore, both effect of Vav2 gene on invasion and metastasis of gastric cancer cells and its mechanism are investigated in vitro. Results showed that positive rate of Vav2 protein was significantly higher in gastric cancer tissues than in adjacent tissues and notably higher in metastatic lymph nodes than in gastric cancer tissues. Results of western blot were consistent with immunohistochemistry. Expression of Vav2 protein in gastric cancer tissues was related to degree of tumor differentiation, lymph node metastasis, and clinical stages. Inhibition of endogenous Vav2 in BGC823 cells led to significantly decreased cell activity, migration, and invasion ability in vitro, and expression of Rac1 , MMP-2 , and MMP-9 decreased, whereas expression of TIMP-1 increased. We concluded that Vav2 might promote invasion and metastasis of gastric cancer by regulating some invasion and metastasis-related genes.